SLEEP DISORDERS AND FATIGUE AMONG EMERGENCY HEALTHCARE WORKERS - Marina Samuneva-Zhelyabova; Karolina Lyubomirova; Todor Kundurzhiev (Journal of IMAB, 2020)
Background: Fatigue and sleepiness during shift work pose a safety risk for emergency healthcare workers. These are factors which can compromise the effectiveness of these workers and as a result, can have detrimental consequences on the workers’ health and overall well-being. A large share of emergency healthcare personnel reports high levels of work-related fatigue and poor sleep. Objectives: Investigation of sleep disorders and mental and physical fatigue among emergency healthcare workers. Material and Methods: The study was conducted among 468 workers in 2 emergency healthcare centres. The male participants were 58.3%, and 41.7% were female. The distribution by position was nurses 35.8%, followed by drivers - 26.1% , doctors - 18.1%, paramedics - 14.2%, and sanitation workers - 5.8%. Statistical methods used included descriptive statistics and Chi-square test. Results: The results showed that the biggest share was that of participants who have sleep disorders at age over 55 years – 41%, while by position, that of the physicians – 46.4%. The levels of physical fatigue were higher among participants from the age up to 35 years – 53.1%, and among paramedics – 59.1%, followed by physicians – 58.3%. Mental fatigue was higher among women – 52.7%. The share of mental fatigue at the end of the working day among doctors was higher - 64.3%. Conclusion: Sleep disorders and fatigue are common among emergency healthcare workers.The levels of sleep disorders and physical and mental fatigue are high and unhealthy.